İbnü’l-Arabî’nin Tercümânü’l-eşvâk’ı: Tecellî İfadesi Olarak Şiir ve Şerh. - Özkan, Zeynep Şeyma (Journal of Islamic Review / İslam Tetkikleri Dergisi, 2026)
This article examines Tarjumān al-ashwāq and its commentary Zahāir al-aʿlāq, two works of Ibn ʿArabī that stand out among his writings due to the number of surviving manuscripts and their prominent place in modern scholarship. It approaches these texts through their composition processes, stylistic features, intended audiences, and the relationship between poetry and commentary. The study analyzes manuscripts found in Turkish libraries, some of which were copied from autograph or holograph exemplars, and reassesses the discussions in modern literature by comparing them with the statements in Ibn ʿArabī’s own prefaces and epilogues. The article first considers the dates of composition and examines the views of Nicholson and Beneito, who approach the claim that Zahāir might represent a rewriting of Tarjumān from different perspectives. It then identifies the points at which the findings of the autograph-based manuscripts do not align with these views. Second, it discusses the context in which the work and its commentary were composed and who they were intended to address, drawing on the expressions found in the prefaces and epilogues. It also demonstrates that the autograph-related manuscripts contradict the claims that the work is a love narrative centered on Nizām, or that the commentary was written to adress criticisms stemming from such a narrative. Finally, the relationship between meaning-form highlighted in studies on Tarjumān and Zahāir is examined within the framework of Ibn ʿArabī’s own views on the subject. Within this framework, the example of Tarjumān is discussed as a domain in which the mode of expressing divine theophany becomes particularized in Ibn ʿArabī’s thought. In conclusion, this study reassesses many of the major assumptions in the literature on Tarjumān and Zahāir by returning to the manuscript evidence. It shows that the reasons for composition, intended audience, and mode of expression in these texts form a coherent whole. This coherence, in turn reflects Ibn ʿArabī’s characteristic expression (the zāhir–bātin approach) that underlies his broader stylistic and intellectual framework.